2013
DOI: 10.1124/jpet.113.207548
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activity of Norhydrocodone: An Active Metabolite of Hydrocodone

Abstract: Hydrocodone is primarily metabolized to hydromorphone and norhydrocodone. Although hydromorphone is a known active metabolite of hydrocodone, the in vivo activity of norhydrocodone is not well documented. In the current study, the pharmacodynamics of norhydrocodone were evaluated and compared with hydrocodone and hydromorphone. Binding studies established that norhydrocodone, similar to hydrocodone and hydromorphone, is a m-selective opioid ligand. In vivo analgesia studies (tail flick) demonstrated that, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Another study reports a maximum peak concentration of 23.6 ± 5.2 ng/mL serum achieved at 1.3 ± 0.3 h (t max ) after a 10 mg oral dose of hydrocodone administered to five adult male subjects. The elimination half‐life (t 1/2 ) for hydrocodone following oral administration in humans is around 4 h for hydrocodone and 8 h for norhydrocodone …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reports a maximum peak concentration of 23.6 ± 5.2 ng/mL serum achieved at 1.3 ± 0.3 h (t max ) after a 10 mg oral dose of hydrocodone administered to five adult male subjects. The elimination half‐life (t 1/2 ) for hydrocodone following oral administration in humans is around 4 h for hydrocodone and 8 h for norhydrocodone …”
Section: Resultsmentioning
confidence: 99%
“…The elimination half-life (t 1/2 ) for hydrocodone following oral administration in humans is around 4 h for hydrocodone and 8 h for norhydrocodone. [38,39,49] We observed a maximum peak concentration in blood of 44.9 ± 1.9 ng/mL hydrocodone and 7.7 ± 0.3 ng/mL norhydrocodone 1 h after intake (Figure 4). These concentrations were reduced by approximately 50% after another 3 h and 8 h for hydrocodone and norhydrocodone respectively (20.5 ± 1.0 ng/mL hydrocodone was measured 4 h after intake and 3.3 ± 0.4 ng/mL norhydrocodone 9 h after intake).…”
Section: Incurred Samplesmentioning
confidence: 86%
“…Interestingly, our acute ED 50 values for hydrocodone are between values reported by two other studies that used the radiantheat tail-flick assay rather than warm-water tail immersion. Kolesnikov et al (2003) found an ED 50 value of 1.37 mg/kg in Swiss Webster mice bred by a different vendor, whereas Navani and Yoburn (2013) calculated an ED 50 value of 11 mg/kg in CD-1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was separated by centrifugation at 2°C within one hour of collection, transferred into polypropylene tubes, and stored at −20°C to −80°C until analysis was performed. Concentrations in plasma of HC and its minor, though active O-demethylated metabolite, hydromorphone, 12 , 13 were determined by a validated assay using liquid chromatography with tandem mass spectrometric detection (LC-MS/MS) (Bioanalytical Services, Athlone, Republic of Ireland). Following solid-phase extraction of HC, hydromorphone, and internal deuterated standards, samples were reconstituted in trifluoroacetic acid and acetonitrile, and loaded onto a liquid chromatography system equipped with a Sciex mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%